Influence of Health Workers and Teachers of SMA 10 RL on the Socialization of Marigold Plants, Cathatarantus Roseus, Ovitrap Fermentation to Minimize Flies, Mosquitoes, and Preventive of DHF - Rustam Aji Rochmat; Dewi Lusiani; Reza Fahlevi (CV. Get Press Indonesia, 2025)
Dengue hemorrhagic fever (DHF) remains a significant public health problem in tropical regions, including Indonesia, due to the rapid spread of Aedes aegypti and Aedes albopictus mosquitoes. Effective prevention strategies require community involvement and awareness. This study examined the influence of health workers and teachers at SMA 10 RL in socializing the use of Tagetes erecta (marigold), Catharanthus roseus, and fermented ovitrap to minimize mosquito larvae and prevent DHF. The research design used a pre-experiment with a one-group pretest-posttest method, involving 90 students selected by purposive sampling. The intervention included educational sessions and demonstration of mosquito control practices. Data were collected through questionnaires and analyzed using the Paired Sample T-Test test. The results showed a significant increase in students' knowledge scores from 57.18 (pretest) to 82.84 (posttest), as well as practice scores from 55.64 to 79.74 (p < 0.05). These findings suggest that the integration of biological-based mosquito control methods in educational programs can increase the effectiveness of dengue prevention. Collaboration between health workers and teachers plays an important role in ensuring effective knowledge dissemination and application. Future research should explore long-term behavioral changes and the potential for implementing similar programs in different educational institutions.